2023
DOI: 10.1371/journal.pone.0281621
|View full text |Cite
|
Sign up to set email alerts
|

Intraspecific variability of the saccular and utricular otoliths of the hatchetfish Argyropelecus hemigymnus (Cocco, 1829) from the Strait of Messina (Central Mediterranean Sea)

Abstract: Mesopelagic species are enjoining increasing attention due to the growing impact of fisheries activities on deep marine biocenosis. Improving the knowledge base on mesopelagic species is required to enhance their conservation due to the knowledge gaps regarding many species and families. In this context, otoliths can be fundamental to assessing their life history, ecomorphological adaptation to the deep environment and stock composition. The present paper aims to explore the saccular and utricular otoliths mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 110 publications
0
9
0
Order By: Relevance
“…The projection described by Gonçalves et al [110] was mainly used in 2D shape analysis to identify stocks, but it cannot be used to analyse the sulcus acusticus. Previous studies have attempted to examine the size and shape of this part of the otolith using 2D shape analysis [111][112][113]. However, these approaches have limitations, as they do not take into account the depth of this structure.…”
Section: Discussionmentioning
confidence: 99%
“…The projection described by Gonçalves et al [110] was mainly used in 2D shape analysis to identify stocks, but it cannot be used to analyse the sulcus acusticus. Previous studies have attempted to examine the size and shape of this part of the otolith using 2D shape analysis [111][112][113]. However, these approaches have limitations, as they do not take into account the depth of this structure.…”
Section: Discussionmentioning
confidence: 99%
“…Sixteen minor and trace elements ( 137 Ba, 111 Cd, 52 Cr, 59 Co, 65 Cu, 7 Li, 25 Mg, 55 Mn, 23 Na 60 Ni, 208 Pb, 85 Rb, 121 Sb, 82 Se, 88 Sr, and 66 Zn), plus the calcium ( 44 Ca), were analyzed with Inductively Coupled Plasma Mass Spectrometry (ICP-MS) using an iCAP 227 TM Q 228 (Thermo Fisher Scientific, Bremen, Germany) instrument equipped with a concentric glass nebulizer, a Peltier-cooled baffled cyclonic spray chamber, a standard quartz torch, and a two-cone interface design (nickel sample and skimmer cones). Argon of high purity (99.9997%, Gasin II, Leça da Palmeira, Portugal) was used as the nebulizer and plasma gas.…”
Section: Otolith Chemical Analysismentioning
confidence: 99%
“…Thus, otoliths are suitable tools to evaluate individual phenotypic geographic variations at the stock, population, or subpopulation level, which requires appropriate sampling designs, methodological approaches, and study goals [9,10,12]. The sagitta is usually the largest and thus the most used in previous studies, although the other otoliths are also useful and informative for these purposes [21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…species-specific features (Callicó Fortunato et al ., 2014; Avigliano et al ., 2016; Ferri et al ., 2018; Mejri et al ., 2022b). In addition, these otoliths have been documented to show variations in morphologies (shape and morphometry) at both the inter and intraspecific levels (Ferri et al ., 2018; Tuset et al ., 2018; Ben Labidi et al ., 2020b; Mejri et al ., 2020, 2022b; Khedher et al ., 2021; D'Iglio et al ., 2023) and their morphometry, in particular, has a close relationship to fish body size (Martucci et al ., 1993). In addition, it has been shown that these variations are influenced by several factors, including genetic (Vignon and Morat, 2010; Berg et al ., 2018), ontogenetic (Hüssy, 2008; Capoccioni et al ., 2011), physiological (Lombarte and Cruz, 2007; Schulz-Mirbach et al ., 2019), phylogeny (Campana and Neilson, 1985; Torres et al ., 2000), and exogenous factors, such as living depth (Wilson, 1985; Lombarte and Lleonart, 1993), temperature (Lombarte and Lleonart, 1993) and salinity of the water (Capoccioni et al ., 2011), and food supplies (Gagliano and McCormick, 2004; Hüssy, 2008; Bremm and Schulz, 2014).…”
Section: Introductionmentioning
confidence: 99%